Four new species of Amblyseiinae (Phytoseiidae, Acari) from the Philippines - Corpuz-Raros, L.A (Asia life sciences :the international journal of life sciences.)
"Four new species of phytoseiid mites belonging to the subfamily Amblyseiinae are described from the Philippines, namely, Asperoseius baguioensis, A. lagunensis, Paraamblyseius foliatus and Proprioseius schichai. Keys to known world species and taxonomic notes are given for the three genera under which the new species are included."